Implementasi Pembelajaran Diferensiasi dalam Meningkatkan Kemampuan Pemecahan Masalah Matematika Siswa SMPN 1 Pacitan: Penelitian - Mulyadi (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
This study aims to determine the differences in mathematical problem-solving abilities between students who received differentiated learning and those who did not. The study was conducted at SMPN 1 Pacitan in the 2023/2024 academic year using a quasi-experimental method using a Pretest–Posttest Control Group design. The study population was all 288 seventh-grade students, with a sample of 64 students consisting of 32 students from the experimental class (VII-D) and 32 students from the control class (VII-F). The research instrument was a descriptive test of mathematical problem-solving abilities that had passed validity, reliability, difficulty level, and discrimination tests, and met normality and homogeneity tests. Data analysis was carried out using the Independent Sample t-Test with the help of IBM SPSS. The analysis results showed a significance value of 0.001 (<0.05), so H1 was accepted, which means there was a difference in the improvement of mathematical problem-solving abilities between the two groups. The average gain score of the experimental group (30.28) was higher than that of the control group (17.44), so it was concluded that differentiated learning had a significant effect on improving the mathematical problem-solving abilities of class VII students at SMPN 1 Pacitan.